Pendidikan Agama Islam di Tengah Arus Globalisasi: Tantangan dan Upaya Antisipasi - Purba, Melisa; Pane, Sinta Sri Mogana; Saragih, Ummi Dearni; Lubis, Reza Noprial (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
Educational values of Islam today is getting late in the tumult of various changes that are the result of the influence of globalization. Globalization has become a historical necessity that many challenges also opportunities in education that will shake up the order of the culture, customs, and values of the noble teachings of Islam. Therefore reformatting the theory and practice of education should be carried out and balanced, so that Islamic education is not passive as a spectator instead of a player, as consumers rather than producers. Islamic education also must perform and portray themselves as agents of change while strengthening Islamic identity.